2015
DOI: 10.1161/hypertensionaha.114.04981
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Mineralocorticoid Receptor Activation Leads to Metabolic Syndrome and Induction of Prostaglandin D2 Synthase

Abstract: M etabolic syndrome (MetS)1 is a disorder of energy use and storage, diagnosed by co-occurrence of at least 3 of 5 of the following medical conditions: abdominal (central) obesity, hypertension, elevated fasting-plasma glucose, high triglycerides, and low high-density lipoprotein cholesterol levels. Clinically, MetS is strongly associated with increased risk of cardiovascular disease and type-2 diabetes mellitus.Adipose tissue plays a central role in the metabolic alterations: adipose tissue is not only the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 36 publications
6
103
0
Order By: Relevance
“…MR is also expressed in nonepithelial cells, including cardiomyocytes (1), vascular cells (2,3) and macrophages (4,5), and has been implicated in pathological conditions such as heart failure, endothelial dysfunction, hypertension, insulin resistance, and obesity (6)(7)(8)(9)(10). Recently, MR has been identified in adipocytes (11)(12)(13)(14). The (patho)-physiological significance of adipocyte MR is unclear, although experimental and human studies have demonstrated increased expression of adipocyte MR in obesity, metabolic syndrome, and diabetes (6,14,15).…”
Section: Mineralocorticoid Receptor (Mr) Expression Is Increased In Amentioning
confidence: 99%
See 4 more Smart Citations
“…MR is also expressed in nonepithelial cells, including cardiomyocytes (1), vascular cells (2,3) and macrophages (4,5), and has been implicated in pathological conditions such as heart failure, endothelial dysfunction, hypertension, insulin resistance, and obesity (6)(7)(8)(9)(10). Recently, MR has been identified in adipocytes (11)(12)(13)(14). The (patho)-physiological significance of adipocyte MR is unclear, although experimental and human studies have demonstrated increased expression of adipocyte MR in obesity, metabolic syndrome, and diabetes (6,14,15).…”
Section: Mineralocorticoid Receptor (Mr) Expression Is Increased In Amentioning
confidence: 99%
“…Recently, MR has been identified in adipocytes (11)(12)(13)(14). The (patho)-physiological significance of adipocyte MR is unclear, although experimental and human studies have demonstrated increased expression of adipocyte MR in obesity, metabolic syndrome, and diabetes (6,14,15). Adipose tissue has long been considered primarily as simple fat storage of triglycerides to regulate several important functions, such as energy balance and thermogenesis, but is now recognized as a metabolically active endocrine/paracrine/autocrine organ that synthesizes, stores, and secretes hormones, vasoactive factors, and proteins, termed adipo(cyto)kines (16,17).…”
Section: Mineralocorticoid Receptor (Mr) Expression Is Increased In Amentioning
confidence: 99%
See 3 more Smart Citations